Synthesis and characterization of semisynthetic analogs of the antifungal occidiofungin - Geng, Mengxin; Hansanant, Nopakorn; Lu, Shi-En; Lockless, Steve W.; Shin, Ronald; Orugunty, Ravi; Smith, Leif (Frontiers in Microbiology, 2022)
Occidiofungin is a broad-spectrum antifungal compound produced by Burkholderia contaminans MS14. It is a cyclic glycol-lipopeptide with a novel beta-amino acid (NAA2) containing a hydroxylated C18 fatty acid chain with a xylose sugar. This study reports a strategy to produce semisynthetic analogs of occidiofungin to further explore the structure activity relationships of this class of compounds. Oxidative cleavage of the diol present on carbons five C(5) and six C(6) removes the xylose and twelve carbons of the fatty acid chain. The resulting cyclic peptide product, occidiofungin aldehyde, is devoid of antifungal activity. However, the free aldehyde group on this product can be subjected to reductive amination reactions to provide interesting semisynthetic analogs. This chemistry allows the quick generation of analogs to study the structure activity relationships of this class of compounds. Despite restoring the length of the aliphatic side chain by reductive amination addition with undecylamine or dodecylamine to the free aldehyde group, the obtained analogs did not demonstrate any antifungal activity. The antifungal activity was partially restored by the addition of a dihydrosphingosine. The dodecylamine analog was demonstrated to still bind to the cellular target actin, suggesting that the diol on the side chain of native occidiofungin is important for entry into the cell enabling access to cellular target F-actin. These results show that the alkyl side chain on NAA2 along with the diol present on this side chain is important for occidiofungin’s antifungal activity.